2014
DOI: 10.1002/ange.201310671
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Chelating Azides for Efficient Click Conjugation Reactions in Complex Media

Abstract: The concept of chelation‐assisted copper catalysis was employed for the development of new azides that display unprecedented reactivity in the copper(I)‐catalyzed azide–alkyne [3+2] cycloaddition (CuAAC) reaction. Azides that bear strong copper‐chelating moieties were synthesized; these functional groups allow the formation of azide copper complexes that react almost instantaneously with alkynes under diluted conditions. Efficient ligation occurred at low concentration and in complex media with only one equiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 34 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…The afforded azidomethyl derivatives of benzimidazole, benzoxazole, and benzothiazole, 3a-c were then allowed to react with terminal acetylenic glucopyranoside sugars 4-6, incorporating the acetylated D-glucose, D-galactose, or D-xylose moiety, under modified copper-catalyzed click 1,3-dipolar cycloaddition to produce the corresponding 1,2,3-triazole-N-linked glycosides 7-9, in 84-96% yields (Figure 3). ethanol/DMF/water in quantitative yields, as previously reported [36,37] (Figure 2). The afforded azidomethyl derivatives of benzimidazole, benzoxazole, and benzothiazole, 3ac were then allowed to react with terminal acetylenic glucopyranoside sugars 4-6, incorporating the acetylated D-glucose, D-galactose, or D-xylose moiety, under modified copper-catalyzed click 1,3-dipolar cycloaddition to produce the corresponding 1,2,3-triazole-N-linked glycosides 7-9, in 84-96% yields (Figure 3).…”
Section: Synthesis Of the Designed Compoundssupporting
confidence: 86%
See 2 more Smart Citations
“…The afforded azidomethyl derivatives of benzimidazole, benzoxazole, and benzothiazole, 3a-c were then allowed to react with terminal acetylenic glucopyranoside sugars 4-6, incorporating the acetylated D-glucose, D-galactose, or D-xylose moiety, under modified copper-catalyzed click 1,3-dipolar cycloaddition to produce the corresponding 1,2,3-triazole-N-linked glycosides 7-9, in 84-96% yields (Figure 3). ethanol/DMF/water in quantitative yields, as previously reported [36,37] (Figure 2). The afforded azidomethyl derivatives of benzimidazole, benzoxazole, and benzothiazole, 3ac were then allowed to react with terminal acetylenic glucopyranoside sugars 4-6, incorporating the acetylated D-glucose, D-galactose, or D-xylose moiety, under modified copper-catalyzed click 1,3-dipolar cycloaddition to produce the corresponding 1,2,3-triazole-N-linked glycosides 7-9, in 84-96% yields (Figure 3).…”
Section: Synthesis Of the Designed Compoundssupporting
confidence: 86%
“…The 2-bromomethyl-derivatives of benzimidazole ( 2a ), benzoxazole ( 2b ), and benzothiazole ( 2c ) were prepared via an adapted procedure as shown in Figure 2 [ 33 , 34 , 35 ]. Azidation of the heteroaryl bromide 2a – c was accomplished in hot ethanol/DMF/water in quantitative yields, as previously reported [ 36 , 37 ] ( Figure 2 ). The afforded azidomethyl derivatives of benzimidazole, benzoxazole, and benzothiazole, 3a – c were then allowed to react with terminal acetylenic glucopyranoside sugars 4 – 6 , incorporating the acetylated d -glucose, d -galactose, or d -xylose moiety, under modified copper-catalyzed click 1,3-dipolar cycloaddition to produce the corresponding 1,2,3-triazole-N-linked glycosides 7 – 9 , in 84–96% yields ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Bevilacqua et al and Kennedy et al also demonstrated cell labelling by CuAAC using similar bis(tert-butyltriazoly) ligand and Cu(II)-bis-L-histidine complex, respectively. 15,16 To overcome this limitation fundamentally and increase the convenience, other chemists have increased the reactivity of alkynes using ringstrain which enables an azide-alkyne reaction without the need for a cytotoxic copper catalyst. These strain-promoted azidealkyne cycloaddition reactions (SPAAC) have favourable second order reaction rate constants (approximately 0.1 M À1 s À1 ) under aqueous conditions without a catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Chelating azides(22) used by Taran and coworkers to form N3-Cu complexes(23) to promote the CuAAC[94].…”
mentioning
confidence: 99%